MENGENAL BERBAGAI MODEL HIDROLOGI DI INDONESIA (Eternitas: Jurnal Teknik Sipil, 2023)
The hydrological model is a simplification of the complexity of a real-world hydrological system of a watershed. Since 1890, various hydrological models have been developed to assist decision makers in formulating watershed management scenarios. This study examines nine hydrological models through a literature review. The nine models are HydroOffice BFI+, HEC-HMS, HEC-SSP, EPA-WMOST, EPA-AGWA, EPA-SWMM, AGNPS, ANSWERS, and ANFIS. The results of the study are briefly explained as follows. Flood analysis could apply one of the tools namely HEC-HMS, AGWA, SWMM, AGNPS, ANSWERS, and ANFIS. However, certain flood analysis programs need to be combined with GIS and HEC-SSP to get an adequate analysis. Baseflow separation analysis could use BFI+ with the daily rainfall as input data. Analysis of the rate of erosion and sedimentation could apply AGWA, AGNPS, ANSWERS. The HEC-SSP model provides assistance in correcting incomplete and inconsistent data. In terms of water resource management on a watershed scale, the WMOST and AGNPS models can be used. However, some types of models have limitations. Therefore, in applying the model, it is necessary to combine several models to get optimal results. In addition, the results of the hydrological model analysis need to be confirmed by field measurements